The Effect of Turmeric and Ginger Powder on Japanese Quail (Coturnix coturnix) Serum Lipid Profile - Meilinda Pahriana Sulastri; Hasan Basri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Lipids are essential fatty acids. Lipids function as a source of energy and structural constituent components of Japanese quails. Japanese quail (Coturnix coturnix japonica) is one of the livestock sectors that is efficient in providing nutrients, both from eggs and meat. However, this animal has high cholesterol levels. This study aimed to determine the effect of organic feed on the cholesterol, triglyceride, HDL (High Density Lipoprotein), and LDL (Low Density Lipoprotein) level of Japanese quail. This study used an experimental method with a completely randomized design (CRD). The test animals were 30 females Japanese quail which were divided into 3 groups (2 individuals each) with different treatments i.e. P0: control (commercial feed); P1: standard organic feed (corn, soybean, bran and fish meal); P2: special organic feed (corn, soybean, bran, fish meal, cassava leaves, turmeric and ginger powder). Each treatment consisted of 5 replications. Feed was given for 2 months and at the end of the treatment, the blood was collected for analysis. Data obtained were analyzed using analysis of variance (ANOVA) and continued with Duncan test with a confidence of 95% (Î±=0.05). Analysis was performed using SPSS software 16.0 for windows. The results showed that the effect of organic feed containing cassava leaves, turmeric and ginger powder is significantly different on live weight, and not significantly different on feed consumption and drinking consumption. Moreover, the provision of that special organic feed was able to stabilize the cholesterol and HDL levels, and reduce LDL levels in Japanese quail (Coturnix coturnix japonica).